Double purse-string suture technique for circular-stapled anastomosis during robotic Ivor Lewis esophagectomy - Zhang, Hanlu; Zuo, Zeping; Yan, Xiuji; Wang, Fuqiang; Yang, Lin; Qiu, Guanghao; Chen, Long-Qi; Wang, Yun (Frontiers in Surgery, 2022)
Background With advantage of the robotic suturing capacity, purse-string suture is technically simple and convenient. This study aimed to present our technical aspects and initial results of robotic Ivor Lewis esophagectomy using two purse-string sutures for circular-stapled anastomosis. Methods After stomach mobilization, gastric conduit formation, esophagus mobilization and two-field lymphadenectomy, the first robotic hand-sewn purse-string suture is applied to the esophageal muscular layer with adequate margin above the tumor. A longitudinal incision in the anterior wall of the esophagus is made and the circular stapler anvil was inserted. The esophagus was transected by scissors 1-cm caudal to the first purse string suture and the purse-string tied to secure the anvil. Then the second robotic hand-sewn purse-string suture is applied to the whole-layer of the proximal end of the esophagus and tied. Finally, the anvil was connected to the body of the stapler and fired. Results The clinical data of ten patients who underwent robotic Ivor Lewis esophagectomy with an intrathoracic circular-stapled end-to-side anastomosis from February 2022 and April 2022 were collected. There were 7 male and 3 female patients, and had a mean age of 63.2 ± 7.6 years. Tissue donuts were complete in all cases and all operations were successfully performed without conversions. The mean overall operative time was 358.2 ± 40.3 minutes. The mean estimated blood loss was 83.2 ± 15.6 ml. The median length of hospital stay was 11.5 ± 4.1 days. All the patients had an uneventful postoperative period. Conclusion Two purse-string sutures are necessary to obtain a tight seal of the esophageal tissue around the anvil to avoid potential anastomotic leak and are an essential process for the safety of circular-stapled anastomosis during robotic Ivor Lewis esophagectomy.